
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.


M = (345 x (6789 + 3456 - 245)/690) x 99/100 x 98/99 x...x 2/3 x 1/2
M = ((345 x 10000)/690) x 99/2 (rút gọn)
M = (10000/2) x 99/2
M = 5000 x 99/2
M = 247500
Ok nha

\(1-\left(\frac{12}{5}+y=\frac{8}{9}\right):\frac{16}{9}=0\)
\(1-\left(\frac{12}{5}+y-\frac{8}{9}\right)=0\times\frac{16}{9}\)
\(1-\left(\frac{12}{5}+y-\frac{8}{9}\right)=0\)
\(\frac{12}{5}+y-\frac{8}{9}=1-0\)
\(\frac{12}{5}-y+\frac{8}{9}=1\)
\(\frac{12}{5}-y=1-\frac{8}{9}\)
\(\frac{12}{5}-y=\frac{1}{9}\)
\(y=\frac{12}{5}-\frac{1}{9}\)
\(y=\frac{108}{45}-\frac{5}{45}\)
\(y=\frac{103}{45}\)

\(x+\frac{2}{3}=\frac{9}{11}\)
\(x=\frac{9}{11}-\frac{2}{3}\)
\(x=\frac{5}{33}\)
\(x-\frac{3}{10}=\frac{4}{15}\)
\(x=\frac{3}{10}-\frac{4}{15}\)
\(x=\frac{1}{10}\)
\(x\times\frac{1}{7}=\frac{5}{6}\)
\(x=\frac{5}{6}:\frac{1}{7}\)
\(x=\frac{35}{6}\)
\(x:\frac{3}{5}=\frac{1}{6}\)
\(x=\frac{3}{5}.\frac{1}{6}\)
\(x=\frac{1}{10}\)
+, \(x+\frac{2}{3}=\frac{9}{11}\)
\(x=\frac{9}{11}-\frac{2}{3}=\frac{5}{33}\)
+, \(x-\frac{3}{10}=\frac{4}{15}\)
\(x=\frac{4}{15}+\frac{3}{10}=\frac{17}{30}\)
+, \(x\cdot\frac{1}{7}=\frac{5}{6}\)
\(x=\frac{5}{6}:\frac{1}{7}=\frac{5}{6}.\frac{7}{1}=\frac{35}{6}\)
+,\(x:\frac{3}{5}=\frac{1}{6}\)
\(x=\frac{1}{6}\cdot\frac{3}{5}=\frac{3}{30}=\frac{1}{10}\)

a) $\frac{{14}}{{18}}:\frac{8}{9} = \frac{7}{9}:\frac{8}{9} = \frac{7}{9} \times \frac{9}{8} = \frac{{63}}{{72}} = \frac{7}{8}$
b) $\frac{9}{6}:\frac{3}{{10}} = \frac{3}{2}:\frac{3}{{10}} = \frac{3}{2} \times \frac{{10}}{3} = \frac{{30}}{6} = 5$
c) $\frac{4}{5}:\frac{{10}}{{15}} = \frac{4}{5}:\frac{2}{3} = \frac{4}{5} \times \frac{3}{2} = \frac{{12}}{{10}} = \frac{6}{5}$
d) $\frac{1}{6}:\frac{{21}}{9} = \frac{1}{6}:\frac{7}{3} = \frac{1}{6} \times \frac{3}{7} = \frac{3}{{42}} = \frac{1}{{14}}$

\(a.\frac{4}{3}-\frac{3}{2}:X=\frac{1}{6}\)
\(\frac{3}{2}:X=\frac{4}{3}-\frac{1}{6}\)
\(\frac{3}{2}:X=\frac{8}{6}-\frac{1}{6}\)
\(\frac{3}{2}:X=\frac{7}{6}\)
\(X=\frac{3}{2}:\frac{7}{6}\)
\(X=\frac{3}{2}\times\frac{6}{7}\)
\(X=\frac{9}{7}\)
\(b.\left(X+\frac{2}{3}\right):\frac{1}{3}=\frac{41}{3}\)
\(X-\frac{2}{3}=\frac{41}{3}.\frac{1}{3}\)
\(X-\frac{2}{3}=\frac{41}{9}\)
\(X=\frac{41}{9}+\frac{2}{3}\)
\(X=\frac{41}{9}+\frac{6}{9}\)
\(X=\frac{47}{9}\)

\(1,\frac{3}{5}+\frac{7}{2}-\frac{4}{7}=\frac{42}{70}+\frac{245}{70}-\frac{40}{70}=\frac{247}{70}\)
\(2,\frac{4}{5}-\frac{1}{3}+\frac{3}{4}=\frac{48}{60}-\frac{20}{60}+\frac{45}{60}=\frac{73}{60}\)
\(3,\frac{1}{3}\times\frac{5}{7}:\frac{7}{2}=\frac{5}{21}:\frac{7}{2}=\frac{10}{147}\)
\(4,\frac{1}{2}:\frac{2}{7}\times\frac{4}{7}=\frac{7}{4}\times\frac{4}{7}=1\)
\(5,\frac{19}{15}\times\frac{3}{7}:\frac{4}{9}=\frac{19}{35}:\frac{4}{9}=\frac{171}{140}\)
\(6,\frac{11}{3}:\frac{9}{16}:\frac{3}{8}=\frac{176}{27}:\frac{3}{8}=\frac{1408}{81}\)
_Chúc bạn học tốt _

\(\frac{2}{3}.\frac{4}{7}=\frac{8}{21}\)
\(\frac{3}{11}.2=\frac{6}{11}\)
\(4.\frac{2}{7}=\frac{8}{7}\)
\(\frac{8}{21}:\frac{2}{3}=\frac{8}{21}.\frac{3}{2}=\frac{21}{2.21}=\frac{1}{2}\)
\(\frac{3}{7}.\frac{7}{3}=\frac{21}{21}=1\)
\(\frac{3}{7}:\frac{3}{7}=\frac{3}{7}.\frac{7}{3}=\frac{21}{21}=1\)
lỡ tay bấm gửi trả lời luôn
\(\frac{2}{3}.\frac{1}{6}.\frac{9}{11}=\frac{2.9}{18.11}=\frac{2.9}{2.9.11}=\frac{1}{11}\)
\(\frac{2.3.4}{2.3.4.5}=\frac{6.4}{6.4.5}=\frac{24}{24.5}=\frac{1}{5}\)
\(\Leftrightarrow x\cdot\dfrac{11}{10}=\dfrac{11}{15}\)
hay x=2/3